Association between dry eye and periodontal disease in community-dwelling Japanese adults: data from the Uonuma cohort study - Kaung Myat Thwin; Noboru Kaneko; Hikaru Okubo; Takayuki Yamaga; Kana Suwama; Akihiro Yoshihara; Masanori Iwasaki; Yumi Ito; Junta Tanaka; Ichiei Narita; Hiroshi Ogawa (BMC, 2024)
Abstract Background While research has explored the risk of periodontal disease in various eye conditions, the link between dry eye and periodontal disease remains underexplored, especially in Japanese adults. This study aims to investigate the association between dry eye and periodontal disease in community-dwelling Japanese adults. Methods This study is a subset of the Uonuma cohort study, which includes Japanese adults aged 40 years and older residing in the Uonuma area of Niigata Prefecture, Japan. Participants completed a self-administered, paper-based questionnaire. Statistical analyses, including the chi-square test, independent t test, ANOVA test, and logistic regressions, were employed to assess the association of periodontal disease with independent variables. Results Among 36,488 participants (average age 63.3 years, 47.4% men), 39.3% had a history of periodontal disease, and gender differences were statistically significant (p < 0.001). Significant associations were found between periodontal disease and dry eye diagnosis or symptoms. Univariable logistic regression revealed links between periodontal disease and age, gender, living status, alcohol consumption, remaining teeth, bite molar availability, and history of dry eye disease or symptoms. Multiple-adjusted regression found that doctor-diagnosed dry eye was associated with a higher likelihood of periodontal disease (odds ratio, 1.12; 95% confidence interval, 1.03-1.22). Participants who never experienced dryness or foreign body sensation had lower ORs of periodontal disease than those who always experienced such symptoms across all models. Conclusion A significant correlation was found between dry eye and periodontal disease in Japanese adults. Regular check-ups, early detection, and effective management of both conditions are strongly recommended.